Stimulation of neurite outgrowth using autologous NGF bound at the surface of a fibrous substrate - Casanova, Marta Alexandra Rodrigues (2022)
Peripheral nerve injury still remains a major clinical challenge, since the available solutions lead to dysfunctional nerve regeneration. Even though autologous nerve grafts are the gold standard, tissue engineered nerve guidance grafts are valid alternatives. Nerve growth factor (NGF) is the most potent neurotrophic factor. The development of a nerve guidance graft able to locally potentiate the interaction between injured neurons and autologous NGF would be a safer and more effective alternative to grafts that just release NGF. Herein, a biofunctional electrospun fibrous mesh (eFM) was developed through the selective retrieval of NGF from rat blood plasma. The neurite outgrowth induced by the eFM-NGF systems was assessed by culturing rat pheochromocytoma (PC12) cells for 7 days, without medium supplementation. The biological results showed that this NGF delivery system stimulates neuronal differentiation, enhancing the neurite growth more than the control condition.